The complete works of Liudprand of Cremona - Liudprand, Bishop of Cremona, -approximately 972 (Medieval texts in translation., 2007)
"This modern English translation of all the surviving literary compositions ascribed to Liudprand, the bishop of Cremona from 962 to 972, offers unrivaled insight into society and culture in western Europe during the "iron century." Since Liudprand enjoyed the favor of the Saxon Roman emperor Otto the Great and traveled to Constantinople more than once on official business, his narratives also reveal European attitudes toward the Byzantine Empire and the culture of its refined capital city. No other tenth-century writer had such privileged access to the high spheres of power, or such acerbic wit and willingness to articulate critiques of the doings of powerful people." "Readers interested in medieval European culture, the history of diplomacy, Italian and German medieval history, and the history of Byzantium will find this collection of translated texts rewarding. A full introduction and extensive notes help readers to place Liudprand's writings in context."--Jacket